Desafios na abordagem diagnóstica de sépsis neonatal precoce - Ana Cláudia Ventura Correia (2021)
Introduction Early-onset neonatal sepsis is a challenging entity, not only due to current epidemiological data and the unique context of the newborn, but also due to the lack of an ideal diagnostic test. The present literature review aims to describe the main limitations in the diagnosis of early-onset neonatal sepsis as well as its implications. Materials and Methods In the original research, 24 articles from Pubmed were selected. Another 2 references were introduced but were not searched in this platform. 17 articles were selected by cross-referencing. Results Newborn's symptons are nonspecific and, often, may be absent even in the presence of infection. Regarding risk factors, these are an important contribution to the suspicion of early-onset neonatal sepsis. Finally, laboratory parameters reveal low sensitivity and specificity being more useful in the exclusion than in the confirmation of sepsis. Nevertheless, blood cultures remain the gold standard. Discussion The detection of early-onset neonatal sepsis requires a high index of suspicion based on symptons, risk factors and laboratory parameters. Thus, it is essential to continue the research work that has been developed over the past years in a perspective of continuous improvement of the diagnostic tools used in the detection of early-onset neonatal sepsis. Conclusion Timely identification of this entity is a huge challenge for specialists, given the limitations inherent to the symptons, risk factors and laboratory parameters presented and discussed in this literature review. Key-words Sepsis; Newborn; Diagnosis